Research Progress on Stability of Slurry Wall Trench of Underground Diaphragm Wall and Design Method of Slurry Unit Weight - Mingfeng Lei; Linghui Liu; Yuexiang Lin; Chenghua Shi; Weichao Yang; Chengyong Cao; Yao Liu (Advances in Civil Engineering)
This paper performs an extensive literature survey and example investigation on the stabilisation of slurry wall trenches during the construction of diaphragm wall panel trenches, and the failure modes of slurry wall trench instability, the stability theoretical analysis models and methods, the slurry formation and its protection mechanism, the influence of related factors on slurry wall trench stabilisation, and other related problems are summarized and analyzed emphatically. And then, based on the limit equilibrium analysis method, the mechanical models of the overall stability and local stability of the trench wall are established, respectively, and the design method of slurry unit weight is derived to ensure the stability of the trench wall. Furthermore, an example application shows that the established slurry unit weight design method is reliable. At last, this paper also proposes the focus and direction for follow-up work, that is, to construct an accurate and effective theoretical analysis model of slurry wall trench instability considering the influence of multiple factors and the calculation method of the slurry cake and its mechanical or mathematical relationship with slurry quality.